2020
DOI: 10.1177/0886260520948142
|View full text |Cite
|
Sign up to set email alerts
|

Why the Victims of Bullying Are More Likely to Avoid Involvement When Witnessing Bullying Situations: The Role of Bullying Sensitivity and Moral Disengagement

Abstract: Recent studies have suggested a link between bullying victimization and passive bystander behaviors, such as more outsider behaviors and fewer defender behaviors. However, little is known about the internal mechanism underpinning this relation. The present study aimed to examine the direct and indirect relationships between bullying victimization and two types of bystander behaviors (defender behavior and outsider behavior), considering the possible mediator role of bullying sensitivity and moral disengagement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 73 publications
4
24
0
2
Order By: Relevance
“…Research on the link between moral disengagement and passive bystanding is still scarce, and the findings are inconsistent. Some studies have found a negative association ( Gini, 2006 ; Thornberg & Jungert, 2013 ), while others have identified a positive association ( Doramajian & Bukowski, 2015 ; Gini et al, 2015 ; Jiang et al, 2022 ; Sjögren et al, 2021 ; Thornberg et al, 2017b ), whereas Mazzone et al (2016) found a nonsignificant association, which was also the outcome in Killer et al’s (2019) meta-analysis. Further research on the association between moral disengagement and passive bystanding is therefore needed.…”
Section: Moral Disengagement Defending and Passive Bystandingmentioning
confidence: 95%
See 1 more Smart Citation
“…Research on the link between moral disengagement and passive bystanding is still scarce, and the findings are inconsistent. Some studies have found a negative association ( Gini, 2006 ; Thornberg & Jungert, 2013 ), while others have identified a positive association ( Doramajian & Bukowski, 2015 ; Gini et al, 2015 ; Jiang et al, 2022 ; Sjögren et al, 2021 ; Thornberg et al, 2017b ), whereas Mazzone et al (2016) found a nonsignificant association, which was also the outcome in Killer et al’s (2019) meta-analysis. Further research on the association between moral disengagement and passive bystanding is therefore needed.…”
Section: Moral Disengagement Defending and Passive Bystandingmentioning
confidence: 95%
“…Children and youth who score higher in terms of moral disengagement more often engage in aggression and bullying (for meta-analyses, see Gini et al, 2014 ; Killer et al, 2019 ), and less often defend victims in bullying situations ( Gini, 2006 ; Jiang et al, 2022 ; Mazzone et al, 2016 ; Pozzoli et al, 2016 ; Thornberg et al, 2015 , 2017b ; for meta-analyses, see Killer et al, 2019 ; Ma et al., 2019 ). Research on the link between moral disengagement and passive bystanding is still scarce, and the findings are inconsistent.…”
Section: Moral Disengagement Defending and Passive Bystandingmentioning
confidence: 99%
“…Accordingly, early adolescents can learn to use moral disengagement from their peers (Caravita et al, 2014). With reference to school bullying, higher levels of moral disengagement are associated with increased bullying (Killer et al, 2019), and lower defending of the victims (Jiang et al, 2020). In some studies, moral disengagement was associated also with higher passive bystanding (Jiang et al, 2020), but the research on this behavior in bullying is still scarce and inconsistent (Mazzone et al, 2016).…”
Section: Moral Disengagementmentioning
confidence: 99%
“…Este tipo de violencia se da de forma grupal en medio de la interrelación entre estudiantes, se manifiesta entre los niños en edad escolar que implica un desequilibrio de poder real o percibido por los estudiantes, tiene un alto potencial de repetirse, con el tiempo. Tanto los niños que son acosados como los que acosan a otros niños, pueden tener problemas graves y duraderos (Jiang et al 2020).…”
Section: Introductionunclassified